A Demythologized Auto/Biography: Beginnings and Evolution of Metabiography in Feminine Postmodern Fiction - Souhir Zekri (European Journal of Life Writing, 2016)
The postmodern features of English fiction like fragmentation and metafictionality seem to find an equivalent in life writing and metabiography. Such instances of metabiography either expose the protagonist in the process of writing a biography or memoir, and/or include extracts of life writings which are textually incorporated in their original format. The aim of this paper is first to explore the structural characteristics of metabiography and its evolution from a theme to a structure/form, through Henry James’s The Aspern Papers (1888), A.S. Byatt’s The Biographer’s Tale (2000) and Marina Warner’s fiction. As Richard Holmes explains, “the boundaries between fact and fiction have become controversial and perilous” (16), boundaries which are crossed by Warner and Byatt, both postmodern female novelists who rely on the plurality of voices and textual collage instead of the conventional omniscient narrator and the linear narrative represented by James. Second, the focus will be on the strategies combining the aesthetic with the ethical, or “the political desire to write the histories of the marginalised, the forgotten, the unrecorded” (Byatt On Histories 10-11) through metabiographical autobiographies and diaries in Warner’s Indigo and The Lost Father. The life writing themes treated in these novels are also studied in relation to the modernist and postmodernist views of reality, history and representation which they reflect.